(untitled) (International Educators Conference, 2025)
Critical thinking is an essential skill for students to succeed in the 21st century. Integrating critical thinking across the curriculum allows learners to develop problem-solving, analytical, and evaluative skills necessary for academic and real-world challenges. This paper explores strategies teachers use to embed critical thinking in various subjects, highlights common challenges, and presents opportunities for improving student learning outcomes. Findings suggest that inquiry-based learning, problem-solving tasks, reflective activities, and interdisciplinary projects are particularly effective. Meanwhile, lack of teacher training, rigid curricula, and time constraints remain key barriers. The study emphasizes the importance of supportive teaching frameworks and professional development to fully implement critical thinking across all subject areas.